Social Capital Function of Community of Tuban Literacy for Collective Action Building Cultural Literacy in Tuban District - Nasikin, Afdolu (Universitas Negeri Surabaya, 2018)
The low literacy culture is a problem that should be our responsibility. Thus, the solution is not only based on formal education, but also paying attention to environmental factors. Because the environment is one of the factors that influence society's habits or interests. So literacy-based social movements should be considered. This study aims to examine the social capital in community of Tuban Literacy and its function to collective action taken to build a youth reading culture in Tuban district. This research takes case study to community of Tuban Literacy. Community Tuban Literacy is a youth community that is engaged to cultivate youth literacy culture in Tuban district. The methodology used in this study is qualitative design with data collection method through observations and in-depth interviews that aim to obtain specific data related to social capital and collective action process undertaken by community Tuban Literacy. Based on the analysis, the social capital of community of Tuban Literacy has a significant effect on collective action. The collective action in the form of activities is Lapak Baca, Tadarus Books, Nggacor sak mbledose, Tour to School, Writing Competition, Cangkruk'an Literacy, Ngamen Literacy, Reading Tree, and Pesantren Literacy. These activities are able to attract teenagers to participate in every community of Tuban Literacy activity. The average ability of young people to read in the community of Tuban Literacy is at the level of literacy. Thus, the output produced is a lot of teenagers whose intensity of reading increases and leads to critical thinking.?Keywords: Community, Social Capital, Collective Action, Literacy Culture